Solve each of the following quadratic equations:

6x^{2} + x - 12 = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 6; b = 1; c = -12

= 6. - 12 = - 72

And either of their sum or difference = b

= 1

Thus the two terms are 9 and - 8

Difference = 9 - 8 = 1

Product = 9. - 8 = - 72

3x(2x + 3)-4(2x + 3) = 0

(2x + 3)(3x-4) = 0

(2x + 3) = 0 or (3x-4) = 0

x = (-3)/2 or x = 4/3

Roots of equation are ,

14